2022
DOI: 10.1155/2022/2147763
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 (HSP90) Inhibitors as Anticancer Medicines: A Review on the Computer-Aided Drug Discovery Approaches over the Past Five Years

Abstract: Cancer is a disease caused by the uncontrolled, abnormal growth of cells in different anatomic sites. In 2018, it was predicted that the worldwide cancer burden would rise to 18.1 million new cases and 9.6 million deaths. Anticancer compounds, often known as chemotherapeutic medicines, have gained much interest in recent cancer research. These medicines work through various biological processes in targeting cells at various stages of the cell’s life cycle. One of the most significant roadblocks to developing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…Numerous drugs inhibit HSP-90, such as those developed to treat cancer that lead to degradation of oncogenic kinase clients of HSP-90. 48 Thus, if the pathway we have identified for degradation of HSP-90 itself in C. elegans is conserved in humans, our findings may have relevance for efficacy of those drugs. Several studies in C. elegans have now shown that reduction of protein quality control factors can paradoxically promote organismal survival.…”
Section: Discussionmentioning
confidence: 77%
“…Numerous drugs inhibit HSP-90, such as those developed to treat cancer that lead to degradation of oncogenic kinase clients of HSP-90. 48 Thus, if the pathway we have identified for degradation of HSP-90 itself in C. elegans is conserved in humans, our findings may have relevance for efficacy of those drugs. Several studies in C. elegans have now shown that reduction of protein quality control factors can paradoxically promote organismal survival.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, it formed a hydrophilic interaction through a water bridge with ASN51. Asn51 was discovered to be an essential residue to interact stably with Hsp90, as reported by Magwenyane [ 51 ]. The hydrophobic interactions were noticed with ALA111, LEU107, LEU103, VAL150, TYR139, PHE138, TRP162, VAL136, VAL186, MET98, ILE96, ALA55, and LEU48 residues ( Figure 6 A and 7A).…”
Section: Resultsmentioning
confidence: 94%
“…Most of the time, scoring abilities can be separated into learning-based and observation-based categories. The latter employ a variety of (frequently physically inspired) terms whose coefficients are advanced using a specific informational index with known binding free energies, in contrast to the former, which use a reversal of the Boltzmann factor to compute scores from the repetition of various perceptions [ 55 , 58 , 59 ].…”
Section: Computer-aided Drug Discovery and Designmentioning
confidence: 99%